The international human right to education - Verhaeghe De Naeyer, Manuella (Department of Public Law, 2023)
Education as a human right is a subject of considerable debate all over the world. Indeed, we are living at a time when concern for educational rights has reached new heights. The importance of the right to education is recognized in several international instruments and in many constitutions but it is also one of the most complex human rights under present international law. In 1954, the United State Supreme Court in the famous case of Brown v Board of Education stressed the fundamental importance of education for all and asserted that "in these days, it is doubtful that any child may reasonably be expected to succeed in life if he (or she) is denied the opportunity of education"